THE EFFECT OF CLIMATE CHANGE ON THE SOCIO-ECONOMIC RESILIENCE OF HORTICULTURAL FARMERS IN MAGETAN REGENCY - Widita Nareswari (CV. Radja Publika, 2025)
This study aims to analyze the influence of climate change on the socio-economic resilience of horticultural farmers in Magetan Regency. Using a quantitative approach with a survey method, this study involved 100 respondents of horticultural farmers spread across several production center sub-districts. The results of the study show that the majority of farmers are aware of climate change which is characterized by erratic growing seasons, rising temperatures, and unstable rainfall. Climate change has a significant impact on farmers' economic aspects, such as declining crop yields, increasing production costs, and reduced net income. From a social perspective, involvement in farmer groups and access to climate information has been proven to strengthen farmers' resilience. However, there are still many farmers who have not implemented optimal adaptation strategies due to limited information, technology, and supporting institutions. This study recommends strengthening local institutions, more intensive climate counseling, and developing participatory adaptation programs as an effort to build resilience in horticultural agriculture in the midst of increasingly intense climate change.